2017
DOI: 10.1177/0379572117731666
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stunting in Children Aged 6 to 59 Months: A Case–Control Study in Southwest Uganda

Abstract: Low access to appropriate complementary diets, sex of child, food insecurity, poor socioeconomic status, and low knowledge about stunting were the main predictors of childhood stunting in the study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
21
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 24 publications
9
21
1
9
Order By: Relevance
“…Unlike many other study findings, this study documented that the odds of being stunted was higher for females as compared to males. This finding is different from other study findings from Ethiopia, Nigeria, Tanzania and Uganda where males have higher risk of being stunted [14,[17][18][19]. On the other hand, in favor of our finding a study from Eastern Ethiopia reported that females had higher chance of being stunted [20].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike many other study findings, this study documented that the odds of being stunted was higher for females as compared to males. This finding is different from other study findings from Ethiopia, Nigeria, Tanzania and Uganda where males have higher risk of being stunted [14,[17][18][19]. On the other hand, in favor of our finding a study from Eastern Ethiopia reported that females had higher chance of being stunted [20].…”
Section: Discussioncontrasting
confidence: 99%
“…We have found that pre-lacteal feeding was a predictor of stunting. This is consistent with a study from Southern and Northern Ethiopia [19,39,40]. The plausible reason may be stunted children are less likely to be introduced to complementary feeding at appropriate age [18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several factors influence stunting, including the socioeconomic status of the household, parents' education, anemia, soil-transmitted helminths (STH) infections, diarrheal infections, dietary intake and complementary feeding [11][12][13][14][15][16][17][18][19][20][21][22]. Short overall duration of breastfeeding, as well as the late introduction of appropriate solid foods, have both been associated with stunting in many studies [18,[23][24][25][26] Birth outcomes such as low birth weight and birth length are also important factors that are associated with higher prevalence of stunting [24,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…A 2017 report noted that approximately, 11 percent of all children were underweight and 2 percent severely underweight with children in rural areas slightly more likely than those in urban areas to be underweight (11 percent and 8 percent, respectively)(9). The western region of Uganda has persistently registered the highest levels of childhood malnutrition especially stunting, yet, this is the region with plentiful food production and is sometimes referred to as "the food basket" of the country (10,11). In the Ankole region of southwest Uganda, children under 5 years 29.3% were stunted, similar to a national average of 29.0% but Buhweju district had stunting levels of 51%-55.6% (9,12).…”
Section: Introductionmentioning
confidence: 99%